Protoflavone-Chalcone Hybrids Exhibit Enhanced Antitumor Action through Modulating Redox Balance, Depolarizing the Mitochondrial Membrane, and Inhibiting ATR-Dependent Signaling - Ahmed Dhahir Latif; Tamás Jernei; Ana Podolski-Renić; Ching-Ying Kuo; Máté Vágvölgyi; Gábor Girst; István Zupkó; Sedef Develi; Engin Ulukaya; Hui-Chun Wang; Milica Pešić; Antal Csámpai; et al. (MDPI AG, 2020)
Hybrid compounds combine fragments with complementary targets to achieve a common pharmacological goal. This approach represents an increasingly popular strategy for drug discovery. In this work, we aimed to design antitumor hybrid compounds based on an inhibitor of ataxia-telangiectasia and Rad3-related protein (ATR)-dependent signaling, protoapigenone, and a pro-oxidant ferrocene or chalcone fragment. Four new triazole-coupled hybrids were prepared. The compounds were cytotoxic against human breast cancer cell lines in vitro, showing IC50 values in the sub-micromolar range. The nature of interactions between relevant fragments of the hybrids was evaluated by the Chou-Talalay method. Experimental combination treatment with the fragments showed additive effects or slight/moderate synergism, while strong synergism was observed when the fragments were virtually combined into their hybrids, suggesting a relevant pharmacological benefit of the coupling. All hybrids were strong inhibitors of the ATR-mediated activation of Chk1, and they interfered with the redox balance of the cells leading to mitochondrial membrane depolarization. Additionally, they induced late apoptosis and primary necrosis in MDA-MB-231 and MCF-7 breast cancer cells, respectively. Our results demonstrate that coupling the ATR-dependent signaling inhibitor protoflavone with a pro-oxidant chalcone dramatically increases the antitumor activity compared with either fragment alone. Such compounds may offer an attractive novel strategy for the treatment of various cancers.